2010
DOI: 10.1016/j.neuropsychologia.2010.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the neural control of locomotion from walking through doorways in Parkinson's disease

Abstract: . (2010) 'Insights into the neural control of locomotion from walking through doorways in Parkinson's disease. ', Neuropsychologia., 48 (9). pp. 2750-2757. Further information on publisher's website:http://dx.doi.org/10. 1016/j.neuropsychologia.2010.05.022 Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Neuropsychologia. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
125
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(149 citation statements)
references
References 45 publications
(57 reference statements)
14
125
4
Order By: Relevance
“…Here, results showed that similar to the previous study, gait worsened in PD when approaching the narrow doorway, however, body-scaled judgments of the doorway width did not differ from those of healthy control participants, and no effects of dopaminergic medication were found (Cowie, Limousin, Peters, & Day, 2010). Therefore, these researchers did not find evidence of a perceptual judgment deficit in PD after they had walked through the doorway, yet FOG was still worse in the narrow width condition.…”
Section: List Of Tablessupporting
confidence: 86%
See 1 more Smart Citation
“…Here, results showed that similar to the previous study, gait worsened in PD when approaching the narrow doorway, however, body-scaled judgments of the doorway width did not differ from those of healthy control participants, and no effects of dopaminergic medication were found (Cowie, Limousin, Peters, & Day, 2010). Therefore, these researchers did not find evidence of a perceptual judgment deficit in PD after they had walked through the doorway, yet FOG was still worse in the narrow width condition.…”
Section: List Of Tablessupporting
confidence: 86%
“…However, those with PD were expected to perform similar to age-matched control participants in static visual perception of distance, since previous studies investigating judgments of size (i.e., doorway width and obstacle height) did not find differences between those with PD and healthy control participants (Cowie et al, 2010;Martens & Almeida, 2011). This would confirm that those with PD are able to correctly perceive the target location and build a spatial representation.…”
Section: The Current Studymentioning
confidence: 74%
“…planning, attention, inhibition, initiation, mental flexibility, fluency, multitasking ...). Recently published results suggested that mental flexibility (set shifting) could be particularly involved [3], while others suggested that impaired visuospatial abilities could interfere with movement planning [22,23]. In addition to frontal lobe dysfunction, imaging data showed that the metabolism of the parietal, occipital and temporal sensory cortices is decreased in patients with FOG [26], which is consistent with the reported visuospatial processing deficits.…”
Section: Discussionsupporting
confidence: 70%
“…As reported, previous studies have shown an association between frontal dysfunction and FOG in patients with PD. 6,7,30 Recent studies 43,44 have demonstrated, by evaluating the influence of space perception on gait in patients with PD, that visuospatial ability appears to be more greatly affected in patients with PD who experience FOG. Furthermore, external visual, mental, and auditory cues (ie, extrinsic drivers) can usually improve FOG.…”
Section: Discussionmentioning
confidence: 99%